The Unsung Evolutionist: Charles Rau's Swiss Lake Dwelling Collection at the Smithsonian Institution - (:unkn) unknown (My University, 2016)
During the second half of the nineteenth century, museums and collectors around the world engaged in a collecting frenzy focused on objects from the Swiss Alpine sites known as Pfahlbauten. Romantic reconstructions of these sites captured the antiquarian imagination and resulted in an artifact diaspora. Charles (Carl) Rau, a German-American archaeologist who became the first Curator of Antiquities at the Smithsonian Institution (SI), collected several hundred Neolithic and Bronze Age artifacts from the lake dwelling sites of Robenhausen and Auvernier, donating this material as well as his library to the SI upon his death in 1886. This thesis investigates the effect of Rau’s political and social evolutionary beliefs on his collecting habits. A detailed object-based investigation in the larger context of the Swiss lake dwelling phenomenon is combined with a close analysis of Rau’s published materials and personal letters held at the National Anthropological Archives (NAA) and Smithsonian Institutional Archives (SIA) to assess his contributions to the development of American archaeology. Similar collections in the United States and Switzerland are compared to the Rau Swiss lake dwelling material to evaluate the impact of individual agency on the development of the SI collection.
Keywords: Carl Rau; Charles Rau; History of Archaeology; Legacy Collections; Smithsonian; Swiss Lake Dweller